Postoperative stroke in head and neck cancer patients submitted to surgery - Silva, Diana P.; Silva, Joaquim C.; Monteiro, Eurico (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Stroke is a highly morbid complication after head and neck surgery (HNS). Our purpose was to report the casuistic of postoperative stroke (POS) in ENT Department of Oporto Cancer Institute, discuss predictable causes and prognosis. Methods: Retrospective study that included cases of POS in our Department, between 2012 and 2017. Medical files were reviewed and perioperative aspects were analysed. Results: We identified 8 cases of POS in 293 HNS performed. All underwent to HNS including bilateral ND as primary treatment. Several cardiovascular risk factors (CVRF) were present, especially carotid artery stenosis (CAS). Complete internal carotid artery (ICA) encasement was present in 2 patients, in whom artery ligation was performed. Acute drop of bispectral index (BIS) occurred in 1 patient. Stroke occurred at 2.8 post-operatory day (in mean) and was ischemic in 7 patients and haemorrhagic in 1. The most affected vessel was cerebral media artery (87.5%). Hemiparesis was the main clinical manifestation (63%). Incidence of POS was 2.7%. Functional and neurologic recovery occurred in 50%. Mortality rate was 37.5%. Conclusions: Our findings suggest that worst outcomes were observed in patients with advanced tumour stages, vessel tumour involvement or carotid artery stenosis presence with requirement ligation of ICA, higher number of CVRF, and low or sudden decrease in BIS values during surgery. According to our results we recommend to screen, select and optimize patients to minimise the incidence and severity of this complication.